WAJAH ISLAM DALAM RUANG BATIN MANUSIA JAWA Menelusuri Jejak Kearifan dalam Naskah Primbon dan Doa - Gusmian, Islah (The International Journal of Pegon : Islam Nusantara civilization, 2018)
So far, studies on Serat Primbon in Java have been focused more on the concept of petung (Javanese reckoning) and mystics living amongpeople. They are rarely connected with the awareness of Islamic symbols and values. This article unravels the close connection between Islamand Javanese wisdom in Serat Primbon dan Doa (Javanese mystical manuals and prayers). It applies Ernst Cassirer’s theory of symbolin order to unveil that connection. According to Cassirer, humans are animal symbolicum able to use symbols to communicate or conveymessages. Humans absorb external cultures and adapt new cultures they develop. Serat Primbon studied in this article is an expressionof the adoption and adaptation of Islamic symbols and values to the awareness of Javanese. For instance, in naming their children, theyadopt names of prophets. They chant prayer formulas by way of Javanese culture and language. They connote various important eventswith the existence of God. In Javanese people’s awareness, symbols are created and meanings are given to activities as a manifestation of theawareness of the ultimate Being and as a form of worship to Him. In this Serat Primbon, Islamic wisdom and Javanese awareness are amalgamated to the extent that both become a distinct awareness.